Finance and Economic Development in the Very Long Run: A Review Essay - Shin, Yongseok (Journal of Economic Literature, 2018)
I review William N. Goetzmann’s Money Changes Everything: How Finance Made Civilization Possible. This magnificent book offers insightful coverage of more than 5,000 years of human history under the theme of “how finance made civilization possible.” I reinterpret its main hypotheses in the context of recent economic research on finance and development, and also compare them with other economic historians’ views. I suggest that further examinations of the historical facts in the book could guide us in rethinking financial regulation. ( JEL E42, E44, G00, N20)